Migration processes in Ukraine: threats in the conditions of the Russian-Ukrainian war - O.V.; A.Y. (Економіка, управління та адміністрування)
The migration processes in Ukraine in the last decade, as well as the issue of the modern migration crisis that arose as a result of the Russian-Ukrainian war, were studied. The perspective of the dynamics of migration as a complex and multifaceted phenomenon is revealed. The features and trends of the migration processes that took place before the beginning of the Russian-Ukrainian war and after the brutal invasion of the russian federation are characterized. The main groups of motives underlying migration processes are analyzed: political, military, economic, social and environmental. The quantitative composition of immigrants in Ukraine was determined and a comparative analysis was made for the last decade. The emigration flows for the purpose of employment and education, which were traced in Ukraine before the war, are identified. The statistical composition of illegal migrants is analyzed. Modern migration challenges caused by the war in Ukraine are identified. The consequences and threats of the migration crisis are analyzed, as well as the advantages are indicated. The problems of integration of Ukrainian refugees into the European community are considered. Emphasis is placed on the positive potential of migration for the development of host states. The peculiarities of the successful policy of re-emigration of Ukrainian refugees are also analyzed.